Audit Klinik Penggunaan Terapi Anti Platelet dan Luaran Klinik untuk Stroke Iskemik di RS Bethesda Yogyakarta - Rizaldy Taslim Pinzon; Iroen Mugiono (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2017)
The quality of healthcare assurance has been established for many years. Clinical audit is adopted as a means of developing high quality care. Clinical audit in daily clinical practice in Indonesia is very limited. The aim of this result was to perform the clinical audit in Ischemic Stroke Care in Bethesda Hospital Yogyakarta. Retrospective cohort study in patients with acute ischemic stroke. The multidisciplinary team performs the clinical audit. The team performed the clinical audit from the stroke registry data. The criteria and standard are established based on the current clinical practice guidelines. The data are obtained from the stroke registry data. The data consist of 713 ischemic stroke patients from January-October 2016. The mortality rate is 6,03%. The standard for anti platelet therapy in all patients with ischemic stroke is not achieved. The variance cases are justified in most cases. In most cases the history of bleeding and large stroke are the main reasons for not prescribing the anti platelet therapy. There are only 10 cases without any justifications. The case study showed that clinical audit can be performed in daily clinical practice. As a cycle the clinical audit should be performed continuously. The use of electronic stroke registry is helpful.